Spatial Quantification of Domestic Water Consumption in Rehankot, Dir Town, Khyber Pakhtunkhwa Province-Pakistan: Spatial Quantification of Domestic Water Consumption - Mahmood, Shakeel; Mayo, Shaker Mahmood; Ihsanullah; Mahmood, Irshad (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
This paper is an effort to quantify and map the water supply system and the spatial distribution of domestic water consumption pattern in the Rehankot- a densely populated area in Dir Town. Perennial River, Springs and Kareez are the main sources of water supply in the area. Public water supply schemes have been developed to collect, and distribute potable water to the community. To assess the water consumption patterns a questionnaire based household survey was conducted using random sampling techniques. Global position system (GPS) was also used to spatially locate the sampling units. Kernal Density Estimation (KDE) was applied to visualize population densities and ordinary Kriging has been used to visualize the spatial trend of domestic water consumption per day. Average daily water consumption has been quantified for different income groups and of different family sizes. High income groups and large families consumption was high. The total water consumption of large, medium and small families was found 912, 526 and 282 liters (l) per day (d) respectively. Whereas, per capita consumption was found very high within medium size families is 70 liters consumption (lc/d) and almost same in small and large size families as 57 and 55 lc/d respectively. Similarly based on income distribution pattern the total water consumption was found directly proportional to their income levels. The overall average per capita consumption was found as 61 l/c/d which are still 9 litres less than the standard consumption value. This study highlights the problems regarding the existing water supply system in the area and the variability of consumption patterns regarding family size and income distribution.